ESl lecturers’ voices on tell me more. - Md. Yunus, Melor; Hashim, Harwati; Jusoff, Kamaruzaman; Mohd Nordin, Norazah; M. Yasin, Ruhizan; Rahman, Saemah (Canadian Academy of Oriental and Occidental Culture, 2010)
In the past, the cost of computers and courseware greatly restricted the use of computers in education. However, computers and courseware are now becoming important tools for learning in the institutions. In order to maximize the utilization of the courseware, it is important to get to know how the teachers perceive the use of the courseware in their classroom. Therefore, this paper aims to investigate how ESL lecturers in a polytechnic in Malaysia perceive the ease of use, usefulness and suitability of a courseware named TELL ME MORE. Data was collected via semi-structured interviews with four ESL lecturers at the polytechnic. Findings show that ESL lecturers indicated positive perceptions on the ease of use, usefulness and suitability of the courseware. However, it was found that the courseware is not quite suitable for the teaching and learning of writing.